Application of Closed Incision Negative Pressure Wound Therapy in Ventral Hernia Repair Surgery Using a Polypropylene Mesh: A Randomized Clinical Trial - Jelinek, Petr; Hrubovcak, Jan; Hajovsky, Radovan; Velicka, Jan; Pies, Martin (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Surgical site infections (SSIs) are a significant complication following ventral hernia repair, potentially leading to prolonged hospital stays and increased morbidity. This study aimed to evaluate whether closed incision negative pressure wound therapy (ciNPWT) reduces the incidence of SSI after ventral hernia repair with polypropylene mesh compared to standard wound care. Materials and Methods: A randomized study was conducted with 100 patients undergoing ventral hernia repair using a polypropylene mesh. Participants were divided into two groups: a control group (n=50), which received standard sterile gauze dressing with an iodine-based disinfectant, and an intervention group (n=50), treated with the ciNPWT system (Vivano® by HARTMANN) for 5 days postoperatively. The primary outcome was the incidence of SSI within one year after surgery. Secondary outcomes included the influence of factors such as age, sex, smoking status, and hernia size on SSI occurrence. The study was approved by the Ethics Committee at the University Hospital Ostrava, adhering to the ethical standards of the Helsinki Declaration. Results: The incidence of SSI was lower in the ciNPWT group compared to the standard care group (4% vs. 12%), though this difference did not reach statistical significance. No significant effect of sex or smoking status on SSI was observed. The control group had a shorter mean length of hospital stay. Larger hernias in the non-ciNPWT group were more prone to SSIs, as expected. Conclusions: Although limited by a small sample size, the findings suggest that ciNPWT may be associated with a reduced rate of SSI following ventral hernia repair. Further studies with larger populations are needed to confirm these results.
Keywords: dospělí; chirurgické síťky; Female; ventrální hernie; terapie ran pomocí řízeného podtlaku; Adult; výsledek terapie; ženské pohlaví; Hernia, Ventral; lidé; Negative-Pressure Wound Therapy; Treatment Outcome; infekce chirurgické rány; Herniorrhaphy; Incidence; Surgical Wound Infection; Male; incidence; operace kýly; Aged; Polypropylenes; lidé středního věku; polypropyleny; mužské pohlaví; senioři; Surgical Mesh; Middle Aged; Humans